Integrated radiochemotherapy study of ZIF-8 coated with osteosarcoma-platelet hybrid membranes for the delivery of Dbait and Adriamycin - Du, Longhai; Zhu, Guanghao; Xu, Yanlong; Han, Binxu; Wang, Yu; Zhu, Minhui; Meng, Yingdi; Chen, Huaiwen; Yu, Zuochong (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract Introduction: The toxic side effects of systemic high-dose chemotherapy and poor sensitivity to radiotherapy hinder the survival rate of patients with osteosarcoma (OS). Nanotechnology offers new solutions for OS treatment, however, conventional nanocarriers suffer from inadequate targeting of tumors and short in vivo circulation time. Methods: Here, we designed a novel drug delivery system, [Dbait-ADM@ZIF-8]OPM, which uses OS-platelet hybrid membranes to encapsulate nanocarriers, to enhance the targeting and circulation time of nanocarriers, thereby enabling high enrichment of the nanocarriers in OS sites. Results: In the tumor microenvironment, the pH-sensitive nanocarrier, which is the metal-organic framework ZIF-8, dissociates to release radiosensitizer Dbait and the classical chemotherapeutic agent Adriamycin for the integrated treatment of OS via radiotherapy and chemotherapy. Benefiting from the excellent targeting ability of the hybrid membrane and the outstanding drug loading capacity of the nanocarrier, [Dbait-ADM@ZIF-8]OPM showed potent anti-tumor effects in tumor-bearing mice with almost no significant biotoxicity. Conclusion: Overall, this project is a successful exploration of the combination of radiotherapy and chemotherapy of OS treatment. Our findings solve the problems of OS insensitivity to radiotherapy and toxic side effects of chemotherapy. Furthermore, this study is an expansion of the research of OS nanocarriers and provides new potential treatments for OS.